2018
DOI: 10.1590/1414-431x20186452
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-3129 promotes cell proliferation in gastric cancer cell line SGC7901 via positive regulation of pRb

Abstract: Several microRNAs (miRNAs) have been reported as oncogenes or tumor suppressors in many cancers, including gastric cancer (GC). However, the role and molecular mechanism of miR-3129 in GC is largely unknown. We aimed to explore the function and the underlying molecular mechanism of miR-3129 in GC. Cancer tissues and corresponding adjacent tissues were collected from 50 patients with GC, and the expression of miR-3129 was detected by RT-qPCR. The expression of miR-3129 and pRb in human GC cell line SCG7091 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…GC is prevalent in East Asia, especially in China. 15 Various miRNAs have been suggested to play important tumor suppressor or oncogenic roles in GC, 8,9 although the mechanisms whereby miRNAs impact the behaviors of GC cells remain unclear. Furthermore, miR-384 has been reported to function as a tumor suppressor in multiple human cancers, but its function in GC has not previously been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GC is prevalent in East Asia, especially in China. 15 Various miRNAs have been suggested to play important tumor suppressor or oncogenic roles in GC, 8,9 although the mechanisms whereby miRNAs impact the behaviors of GC cells remain unclear. Furthermore, miR-384 has been reported to function as a tumor suppressor in multiple human cancers, but its function in GC has not previously been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that miRNAs act by regulating downstream tumor-associated genes. 813 It is therefore necessary to investigate the targets of miR-384 in GC to determine the mechanisms underlying its role in the progression of GC. Using mechanistic assays (luciferase reporter assay and western blot), we demonstrated that MTDH was a direct target of miR-384.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, accumulating evidence demonstrated that microRNAs (miRNAs), as a class of endogenous noncoding short RNA serve as oncogenes and onco-suppressors in diverse human carcinogenesis including GC [6][7][8][9]. Many of them are associated with crucial biological processes, such as cell proliferation, metastasis, and invasion, by regulating relevant targets gene expression at post-transcriptional levels.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogenic role of miR-3129-5p is found in various cancers, including epithelial ovarian cancer and gastric cancer. 22,23 Interestingly, adipocyte-derived extracellular vesicle miR-3129-5p is reported to increase macrophage cholesterol efflux capacity, which may be a predictor for cardiovascular disease. 24 Here, we found that the relative expression of miR-3129-5p was found to be gradually elevated with the increase in Gensini score, indicating that the expression of miR-3129-5p correlated with the increase in coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic role of miR‐3129‐5p is found in various cancers, including epithelial ovarian cancer and gastric cancer 22,23 . Interestingly, adipocyte‐derived extracellular vesicle miR‐3129‐5p is reported to increase macrophage cholesterol efflux capacity, which may be a predictor for cardiovascular disease 24 .…”
Section: Discussionmentioning
confidence: 99%